Calcification of the Atlanto-Occipital Ligament (Ponticulus Posticus) in Orthodontic Patients: A Retrospective Study - Di Venere, Daniela; Laforgia, Alessandra; Azzollini, Daniela; Barile, Giuseppe; De Giacomo, Andrea; Inchingolo, Alessio Danilo; Rapone, Biagio; Capodiferro, Saverio; Kazakova, Rada; Corsalini, Massimo (Healthcare (Basel), 2022)
Background: Ponticlus Posticus (PP) is a rare anomaly of the first cervical vertebra easily identifiable in lateral cephalometric radiograph and typically required for orthodontic diagnosis. The aim of this study is to evaluate the PP prevalence in lateral Cephalograms in a cohort of orthodontic patients treated at the Dental School of the University of Bari ‘Aldo Moro’, Italy, and to find possible connection between PP and other dental anomalies, as well as the patient’s cephalometric characteristics. Methods: A total of 150 panoramic radiographs and 150 lateral Cephalograms, obtained for orthodontic use only, were evaluated. No patients were referred to for congenital syndromes or disease, or a history of previously occurred maxillofacial trauma. A detailed cephalometric study was performed for each patient, and the whole cohort was divided according to the common three dental malocclusion classes. The values obtained were analyzed using the Chi-Square Test. Results: PP prevalence was 8% (12 of 150 cases), where the complete and partial forms observed 4.7% and 3.3%, respectively. Although females were more affected (9.6%), no statistically significant sex-related difference was found. Furthermore, no statistically significant relationship regarding age or dental anomalies (dental agenesis/palatal impacted canines) among the groups was observed either. Cephalometric analyses revealed that half of the subjects with PP were sagittal skeletal class I and had vertical hyper-divergence. Conclusions: PP is a frequent anatomical variation of the cervical vertebra, apparently unrelated to the skeletal malocclusion type or dental anomalies. The current study needs to further confirm the congenital hypothesis of PP’s origin already reported in literature.